Mexico's ports in the global village: concepts and methodology for their study (1982-2004) - Ojeda Cárdenas, Juan (2009)
The policy of trade liberalization that characterizes the neoliberal economic model applied by Mexico demands a different role for ports. Globalization brings winning regions and losing regions. An examination of the reality of Mexico's port regions in the last 20 years shows a change in the hierarchies. In this research we study the competition between ports. To evaluate the ports in this work we take into account the geographical location and physical conditions and infrastructure, the frequency of vessels, as well as the quality and availability of services. The new port geography of Mexico shows the primacy of some major ports. Differences are also established between a disconnected port.